algebra
posted by G .
9x+6y=3 and 3x7y=26 using the substitution method

9x+6y=3 (1)
3x7y=26 (2)
using substitution method in (1) we get
9x+6y=3
dividing by 3 both side we get
3x+2y=1
taking 2y to the other side (here 2y in + so when we change its side it will be )
3x=12y
(here 3 is multiply with x so when it goes other side sign will change in divide)
x=(12y)/3 (3)
3x7y=26 (2)
putting the value of x in (2) from (3)
3*(12y)/37y=26
(3 will cancel by 3)
12y7y=26
19y=26
taking constant no. Same side
9y=261
9y=27
(both sides minus sign will cancel by each other)
9y=27
y=27/9
y=3
putting the value of y in (3)
x=(13*2)/3
x=(16)/3
x=5/3
(u can check ur ans by putting the value of 'x' and 'y' in (1) and (2))